Prospects of Introduction of Mahonia Aguifolium in Uzbekistan (Texas Journal of Agriculture and Biological Sciences, 2022)
The article summarizes the findings of a study on the ornamental features of the mahonia aguifolium, a plant introduced to Uzbekistan for ornamental purposes. In most tree species, the degree of yearly ripening of branches affects how successfully they can overwinter. The lignified portion of mahonia aguifolium shoots averages 75% of their whole length. They have three distinct color phases: crimson when in bloom, dark green in the summer, and reddish-golden-bronze in the fall. The flowers are about 8 mm in diameter, collected in many-flowered panicles or brushes in the axils of the outer scales of the apical bud, light yellow, bright, often with a lemon tint. Sepals 9, greenish-yellow; petals and stamens 6 each. Fruits are juicy berries. Berries are oblong-elliptical, up to 10 mm long, up to 8 mm wide, bluish-black, with abundant bluish bloom oblong-elliptical, up to 10 mm long, up to 8 mm wide, bluish-black, with abundant bluish bloom, covered with 2-8 seeds, sweet and sour. Oblong, chestnut, lustrous seeds measure 4.5 mm long, 2.3 mm diameter, and 1.5 mm thick. There are 5,000 berries or 100,000 seeds per kilogram